Another Theology Is Possible: Exploring Decolonial Pathways - Cormie, Lee ca. 21. Jh. (Toronto journal of theology, 2017)
This paper is written from the perspective of a theologian in the global North with decades-long engagement with the new voices of the Global South. In this paper, I address questions that unfold differently in different contexts but that, ultimately, are shared by all concerning the future of life on planet Earth, the role of humanity in (mis)shaping it, and the shifting horizons of hope and faith. In looking for resources to illumine this divided and rapidly changing world, I focus in particular on Latin American decolonial thinking, less on the thinkers themselves in their own contexts with their own internal debates and more on points of reference for further theological and ethical dialogue. In particular, I wish to (1) sketch the historical context that gave birth to this movement; (2) note defining insights that resonate with liberation theological concerns in drawing new maps of the world and promising paths forward; (3) in particular, in light of expanding awareness of the epistemic violence at the heart of modern Eurocentric and American-centric projects for global order since the sixteenth century, point to new epistemological openings for hope and faith; and (4), in conclusion, insist that in historically unprecedented ways religious questionsand our responses to themlie at the heart of the struggles over the future.